Fracture admissions after burns: A retrospective longitudinal study - Duke, J.; Randall, Sean; Fear, M.; Boyd, James; Wood, F. (Pergamon Press, 2017)
© 2017 Elsevier Ltd and ISBI.Background: Severe burn triggers systemic responses that result in reduced muscle mass and changes in bone formation, with recent evidence also suggesting systemic effects on bone after minor burns. The aim of this study was to assess if people hospitalised with a burn have increased admissions for fractures after discharge. Methods: A population-based longitudinal study using linked hospital morbidity and death data from Western Australia was undertaken of all persons hospitalised for a first burn (n = 30,997) during the period 1980-2012. Australian population-based annual rates for fracture admissions for the period 1993-2012 were obtained from the Australian Institute of Health and Welfare. Rates of hospital admissions for fractures in the burn cohort and the Australian population were standardised, using the direct method, to the age and gender structure of the Western Australian population at the 2006. Annual standardised fracture admission rates for the period 1993-2012 were graphed with estimated 95% confidence intervals. Age and gender specific fracture rates were also examined. Results: A total of 4004 members of the burn cohort had at least one fracture admission for a total of 6096. The median (IQR) time to the first fracture admission after burn was 6.9 years (2.8-13.6) and the median age (IQR) at first fracture admission was 31 years (20-49). The burn cohort experienced admissions for fractures at a rate approximately twice that of the Australian population. While rates were generally higher for males in the burn cohort when compared with males in the Australian population, female burn patients had significantly higher rates over the entire study period when compared with the female Australian population. Elevated rates were observed for those younger than 20 years at the time of the burn admission; however, rates were significantly and consistently elevated during the study period for those 20 years and older at the time of the burn. Conclusions: Burn patients experienced significantly higher age and gender standardised rates of admissions for fractures after discharge from hospital for their index burn. Further prospective research is indicated to clarify any underlyling pathogenic processes linked to the burn that may increase a patient's risk of having a fracture serious enough to undergo admission.